METODE MENUMBUHKAN MINAT BELAJAR ANAK MENURUT PENDIDIKAN ISLAM - Aldiawan (Musawa: Journal for Gender Studies, 2021)
Fostering children's interest in learning is very important because interest is the most convincing foundation for the success of the existing learning process. Ensuring for the success of the learning process of the children is important. Therefore, the children may develop the potential of interests in themselves, so without coercion the children will learn on their own. Basically, there are three factors that influence the emergence of children's interest in learning, which are talent, environmental influence and individual interest. Talent is one of the factors that children are born with, so talent is not something that has happened. It is not formed when an individual is born, but only potentials. Environment, interest in the development of one's life, therefore life between the environment and the family must be improved. Individual interest, in this case the state of one's health, greatly influences the emergence of interest, therefore the health of the body must also be maintained, both from internal and external disturbances.